Production of the AA2196-TiB2 MMCs via PM Technology - Tan, E.; Kaplan, Y.; Ada, H.; Aksöz, S. (Springer International Publishing, 2019)
In this study, metal matrix composite (MMC) materials were produced via powder metallurgy (PM) technology. Main matrix was obtained with AA2196 (Al-Li Alloy) and TiB2 was used as reinforcement materials. In study; TiB2 reinforcements ratio were chosen between 5 and 15%wt. The metallographic investigation was realized with; SEM, EDS, FASTMAP, Optical Microscope analyzing techniques. Hardness values were obtained with HV1. In the study, the reinforcements could be distributed in main matrix homogeneously, via PM technique. The MMCs hardness values increased with the edition of TiB2 reinforcement.
Keywords: FastMap; Al-Li alloys; Powder metals; Lithium alloys; Reinforcement materials; Hardness values; Binary alloys; Aluminum alloys; Reinforcement; Metallic matrix composites; Light metals; Powder metallurgy; Hardness; SEM; AA2196-TiB2 MMCs; Titanium alloys; Powder metallurgy technologies; FASTMAP; Scanning electron microscopy